Investigation of the stretch-shortening cycle performance of youth female volleyball players according to different biological maturation and training status - Mavili, C.; Celik, H.; Unver, E.; Zengin, H. Y.; Cinemre, S. A. (Perceptual and Motor Skills, 2025)
Purpose The aim of this study was to investigate the effect of biological maturation and training status on stretch-shortening cycle (SSC) performance in youth female athletes.